2017
DOI: 10.1088/1361-6463/aa8fef
|View full text |Cite
|
Sign up to set email alerts
|

SERS on paper: an extremely low cost technique to measure Raman signal

Abstract: Finding a low cost substrate for surface-enhanced Raman spectroscopy (SERS) yielding enhanced, reproducible Raman signal from Raman active samples has been a longstanding goal for researchers for years. Herein, we demonstrate the fabrication of such a SERS substrate from paper. The proposed paper-based SERS substrate was developed by attaching polyvinylpyrrolidone (PVP) capped silver nano-particles (AgNPs) to printing grade paper. The performance of the substrate has been evaluated for paper substrates of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…A detailed literature survey revealed that a variety of papers were used (as a base material) for preparing the SERS substrates such as filter paper 71 , chromatography paper 72 , A4 sized paper 73 , tissue papers 74 , and different GCM grade papers 75 . The porosity of the paper (which is typically a few μm) will affect the retention of NPs on its surface.…”
Section: Paper-based Sers Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed literature survey revealed that a variety of papers were used (as a base material) for preparing the SERS substrates such as filter paper 71 , chromatography paper 72 , A4 sized paper 73 , tissue papers 74 , and different GCM grade papers 75 . The porosity of the paper (which is typically a few μm) will affect the retention of NPs on its surface.…”
Section: Paper-based Sers Substratesmentioning
confidence: 99%
“…Finally, the optimized SERS substrate was used to detect phenylethanolamine A and metronidazole with a LOD of 5 nM and 200 nM. Lan et al 74 . reported the inkjet-printed paper-based semiconducting (MoO 3−x ) SERS substrates to detect CV and MG on the fish surface by swabbing.…”
Section: Paper-based Sers Substratesmentioning
confidence: 99%
“…The penetration of NPs into the paper depends on various factors such as the porosity (pore size), thickness, and hydrophobicity. 18 FP was cut into small strips (1 cm 2 ) and then soaked in the prepared NP colloids. The association of the NPs on to the paper was obvious because the color of NPs colloidal solution decreased and became colorless, which means they essentially have got transferred to the FP.…”
Section: Experimental Detailsmentioning
confidence: 99%
“…Unlike glass, it does not exhibit fluorescence. Although the uses of Al-foil (Martínez-Torres et al, 2015), paper (Chamuah et al, 2017), or sandpaper (Fan et al, 2014) are cost-effective as SERS substrate, they are suffering from poor stability and are too flexible to store for a long time. Periodic nanoholes on Al substrate (Lee et al, 2015) have also been employed as SERS substrate; however, it involves high cost due to the use of advanced techniques such as electron beam lithography, focused ion beam, and soft lithography (Kahraman et al, 2017).…”
Section: Fig 3 Uv-vis Absorption Spectrum Of Chemically Synthesized Agnps (Red Line) Commercially Available Agnps (Black Line) and Aunps mentioning
confidence: 99%
“…Aluminum and copper foil (Gudun et al, 2017;Markelonis et al, 2015;Jiang et al, 2013) have the disadvantage of being too flexible, making the surface nonuniform. SERS on paper are not adequately stable, and the signal intensity decreases significantly just after a few days (Chamuah et al, 2017…”
Section: Introductionmentioning
confidence: 99%